MOTIVATION, COMPETENCY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF GOVERNMENT OFFICERS IN BALI PROVINCE IN GENDER PERSPECTIVE ON WORK SATISFACTION - Gusti Ayu Sugiati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research objective was to analyze motivation, competence, job satisfaction and OCB from a gender perspective, the influence of motivation, competence on job satisfaction and OCB. Research respondents were 388 people. Research data with primary data and questionnaires. Hypothesis testing uses SEM analysis with AMOS applications. The results of the study stated (1) from a gender perspective, female officials have lower work motivation, but have higher competence, job satisfaction, and OCB compared to male officials. (2) Motivation has a significant effect on job satisfaction, (3) Motivation has a significant effect on OCB, (4) Competence has a significant effect on Job Satisfaction, (5) Competence has a significant effect on OCB (6) Job Satisfaction has a significant effect on OCB employees (7) Job satisfaction mediates and is significant on motivation and OCB, in mediating the influence of competence on OCB. Important findings from the research on developing the OCB dimensions, from five dimensions, namely altruism, civic virtue, thoroughness, politeness and sportsmanship, became seven dimensions by justifying and adding dimensions of accountability and transparency. Seen from a gender perspective, the dimensions of altruism, civic virtue, and accountability are more dominant in men, while women are more dominant in showing the dimensions of politeness, sportsmanship, thoroughness, and transparency.